The Word Beautiful (al-jameel) in the Holy Qur’an According to Interpreters - Alyabroudi, Yusra Ahmad (Dirasat: Shari'a and Law Sciences, 2020)
This study aims at extrapolating meanings and connotations of the word “beautiful” in (Tafseer) interpretation books according to its mentioning in the Qur’an. The study was based on recognizing places of its mentioning in specific verses, demonstrating it's linguistic and terminological meaning and revealing its concept and connotations according to the context of its mentioning. The inductive approach was used through extrapolating places where the word “beautiful” was mentioned, followed by the analytical approach through recognizing interpreters’ analysis and interpretations for the concept and connotations of the word “beautiful” to clarify its good impact in the human life. The study reached several results, including: the word beautiful is mentioned in the Holy Quran in eight places, seven of which are in the form of beautiful, and one of them in the form of beauty. The return of moral beauty in the Holy Qur'an is followed by several meanings and recipes in seven places, through which the beautiful acquired various connotations, including patience, forgiveness, parting, release and beautiful abandonment. Therefore, the diversity of the semantics of the word beautiful led to the diversity of its interpretation in Tafsir books.